Strategi Pengelolaan Pembelajaran Pada Pendidikan Anak Usia Dini Pasca Pandemi Covid-19 Paud Angkasa Di Bawah Penyelenggaraan Yayasan Ardhya Garini - Putranti, Adim Dwi (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
The COVID-19 pandemic that has occurred for more than 2 years has had an impact on various sectors, including the management of Early Childhood Education learning. This pandemic has made all stakeholders, academics, organizers, managers, educators, and parents of early childhood aware of the need to adapt to a learning management process that can keep up with technological developments and still pay attention to the growth and development of early childhood. This research aims to analyze the learning process strategy in Early Childhood Education (PAUD) after the COVID-19 pandemic in Angkasa PAUD (Playgroup and Kindergarten) under the management of the Ardhya Garini Foundation. This research method uses qualitative, namely data obtained from the results of analysis in the field through observation, interviews, and documentation. The research was conducted at 4 PAUD institutions, namely TK Angkasa 2 Raja Haji Fisabilillah Tanjung Pinang, TK Angkasa 1 Husein Sastra Negara Bandung, TK Angkasa Adi Soemarmo Solo and TK Angkasa Pattimura Ambon. The research results show that PAUD institutions under the management of the Ardhya Garini Foundation implement learning management strategies by planning, organizing, implementing, and supervising which have been implemented well. The challenge faced by the Ardhya Garini Foundation as a PAUD organizer is the equal distribution of the quality of education in KB/TK Angkasa throughout Indonesia. This research will be a very interesting reference for further discussion for policymakers, academics, practitioners, organizers, managers, and PAUD educators regarding strategies for managing PAUD learning centers that are affordable and can be implemented after the Covid-19 pandemic while still paying attention to and prioritizing the rights of children. early childhood rights.